(untitled) (Proceedings of the International Conference on Public Health, 2025)
Applying the Safe Work Permit System (SIKA) training is one approach to reduce the number of accidents. Before implementation, SIKA training is crucial as it lays the groundwork for field implementation, followed by a supervision process, weekly audits, and monthly reviews. The SIKA training material provided consists of six material modules, namely SIKA basics, organization-role-responsibility, risk assessment, permit-to-work, audit, and energy isolation. This study adopts an intervention method by providing training designed to evaluate the effectiveness of training in improving participants’ understanding of work safety. It aims to evaluate the effectiveness of SIKA training in improving workers’ understanding of safety. We used a quantitative approach to conduct a statistical analysis of the collected data, which involved a total of 187 participants divided into 8 training batches. This study employed the paired T-test as its statistical test. The paired sample test’s significance value of 0.001, smaller than alpha, leads to the rejection of H0 and the acceptance of H1. Safe Work Permit System Training has a significant impact on improving understanding of work safety. The number of participants who were above the passing grade when the pre-test was only 42 participants (22.46%) increased dramatically to 144 participants (77.01%). SIKA training shows its effectiveness in improving understanding of work safety through a significant increase in results between pre-test and post-test results. However, we need to implement individual monitoring and evaluation after training to close the understanding gap.